2017
DOI: 10.1002/oby.21860
|View full text |Cite
|
Sign up to set email alerts
|

Exercise's effect on mobility disability in older adults with and without obesity: The LIFE study randomized clinical trial

Abstract: ObjectiveSome data suggests that obesity blunts the benefits of exercise on mobility in older adults. We tested the homogeneity of the effect of a physical activity intervention on major mobility disability across baseline obesity classifications in the Lifestyle Interventions and Independence for Elders (LIFE) Study. LIFE randomized 1,635 sedentary men and women 70–89 years to a moderate intensity physical activity (PA) or health education (HE) program.MethodsMajor mobility disability (MMD), defined as the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…High carbohydrate intake in Korean older adults leads to lower percentage of protein uptake in macronutrients. In addition, while exercise is well known to have positive effects on mobility decline 45 , a previous systematic review of seven controlled trials revealed that dynamic endurance training such as walking, jogging, and cycling, which are easily performed as home-based exercise, has a favourable effects on most of MetS features 46 . Therefore, for older Korean population, replacing carbohydrate with meat, fish, egg, bean, and performing endurance exercise is needed for prevention of both MetS and mobility decline.…”
Section: Discussionmentioning
confidence: 99%
“…High carbohydrate intake in Korean older adults leads to lower percentage of protein uptake in macronutrients. In addition, while exercise is well known to have positive effects on mobility decline 45 , a previous systematic review of seven controlled trials revealed that dynamic endurance training such as walking, jogging, and cycling, which are easily performed as home-based exercise, has a favourable effects on most of MetS features 46 . Therefore, for older Korean population, replacing carbohydrate with meat, fish, egg, bean, and performing endurance exercise is needed for prevention of both MetS and mobility decline.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy lifestyle was determined as previously defined. 18,19,23,24 Participants were asked questions regarding four lifestyle habits, with responses categorized as “always,” “usually,” “seldom,” or “never.” For evaluation, responses were combined as usually/always and never/seldom. Regular exercise was determined according to whether participants usually/always exercised for >30 min, at least three times per week, or seldom/never engaged in exercise.…”
Section: Methodsmentioning
confidence: 99%
“…Healthy lifestyle was determined as previously defined. 18,19,23,24 Participants were asked questions regarding four lifestyle habits, with responses categorized as "always," "usually," "seldom," or "never." For evaluation, responses were combined as usually/always and never/seldom.…”
Section: Cigarette Smoking Was Determined By Asking Eachmentioning
confidence: 99%
“…Exercise incorporating aspects of both aerobic endurance training (AT) and progressive resistance training (RT) does not result in significant weight loss in the absence of CR, but it does exert positive effects on body composition, improve physical function, increase strength, and positively affect quality of life in aging adults with obesity [6 ** ]. A recent study showed that even older adults with class 2+ obesity (BMI ≥ 35 kg/m 2 ) can safely perform moderate intensity physical activity and benefit in terms of mobility [14*]. While CR and exercise both individually improve physical function and quality of life, CR with concurrent exercise training yields better results than either modality alone [15].…”
Section: Exercise Trainingmentioning
confidence: 99%